Referenciação e humor em charges políticas - Blois, Maria Tereza Cattacini (2014)
This study aims to identify and analyze referencing as a strategy in building humor in editorial cartoons. The above mentioned objectives were motivated by the observation of political cartoons regarding the mensalão scandal, in which we found the recurrence of referencing in cartoons creation process, thus revealing the writer s communicative purpose and guiding the reader in the construction of meaning. To achieve our purpose, we built up the corpus of this study with eleven cartoons from the newspaper Folha de S. Paulo, selected between August and October 2012, about the judgment treated by the media as the biggest corruption case in the Brazilian political history, and we proceeded the analysis based on the referencing studies as those performed, today, in the field of texts studies in an interactional sociocognitive perspective as well as on humor studies. In this investigation, we found out that referencing builds the humorous speech through different modalities of language, allowing the construction of the subject in the cartoon review also influencing the meaning effects promoted by the written media. Moreover, we have observed the mensalão - which is the main topic of the cartoons - and we have found out through the present analysis that the subject is classified and reclassified in the discursive activity, in which the politician image is projected, thereby influencing the opinion of newspaper readers